The Role of Islamic Education in Preserving Cultural Identity Amidst Global Modernity - Rahman, Najib Aulia; Azzahra, Aisha (Yayasan Sinergi Kawula Muda, 2024)
This study presents a comprehensive narrative review examining the intersection of Islamic education and cultural identity construction in the context of global modernity. The research investigates how Islamic educational institutions navigate the tension between maintaining traditional religious values and adapting to contemporary global demands. Employing a narrative review method, the study synthesizes evidence from diverse empirical studies and theoretical frameworks that explore both structural and pedagogical dimensions of identity formation. Key findings indicate that Islamic identity is not a static entity but a dynamic construct shaped through selective adaptation, where traditional and modern elements coexist. Educational institutions such as pesantren and Islamic universities employ formal curricula alongside hidden curricula, which together shape students' values and beliefs. However, systemic challenges such as bureaucratic rigidity, limited infrastructure, and misaligned policies hinder effective identity development. The discussion integrates postcolonial and interdisciplinary theories to critique Western-centric educational models and advocate for culturally grounded approaches. The study concludes that responsive educational reforms, inclusive stakeholder collaboration, and strategic digital integration are crucial for sustaining Islamic identity in the modern era. This review underscores the need for culturally sensitive policy frameworks and calls for future research to explore hybrid educational models across diverse sociopolitical contexts.